2017 IEEE 19th International Workshop on Multimedia Signal Processing (MMSP) 2017
DOI: 10.1109/mmsp.2017.8122238
|View full text |Cite
|
Sign up to set email alerts
|

Quality of experience in UHD-1 phase 2 television: The contribution of UHD+HFR technology

Abstract: Abstract-A key factor to determine the quality of experience (QoE) of a video is its capability to convey the large spectrum of perceptual phenomena that our eyes can sense in real life. In order to meet this demand, the recent DVB UHD-1 Phase 2 specification employs new video features, such as higher spatial resolutions (4K/8K) and High Frame Rate (HFR). The first enables larger field of view and level of details, while the second offers sharper images of moving objects going well beyond the current frame rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…For the purpose of the UHDTV signal definition, several studies further investigated the importance of HFR for television [9], [11], [25]. Emoto et al [25] showed that increasing the frame-rate from the traditional 60 fps to high frame-rate of 120 fps provides a significant visual quality improvement.…”
Section: A High Frame-rate Videomentioning
confidence: 99%
See 2 more Smart Citations
“…For the purpose of the UHDTV signal definition, several studies further investigated the importance of HFR for television [9], [11], [25]. Emoto et al [25] showed that increasing the frame-rate from the traditional 60 fps to high frame-rate of 120 fps provides a significant visual quality improvement.…”
Section: A High Frame-rate Videomentioning
confidence: 99%
“…Salmon et al [11] have also studied HFR for television, showing that at least 100 fps is required for improvements over HDTV, especially for content with high motion such as sports. Recently, with one of the first 65 inches UHD HFR prototype displays, Hulusic et al [9] studied the joint and independent contributions of 4K resolution and HFR. The subjective tests carried out showed that the 2160p100Hz format enables a significant increase in visual quality over other configurations -1080p50Hz, 1080p100Hz and 2160p50Hz -but also that the improvements are strongly content dependent.…”
Section: A High Frame-rate Videomentioning
confidence: 99%
See 1 more Smart Citation